Growth and physiological quality in clonal seedlings of Robusta coffee (Revista Ciência Agronômica, 2020)
The intrinsic characteristics of the vegetative propagule may influence the rooting speed and shoot growth,as well as the final physiological quality of clonal seedlings of Coffea canephora. The aim of this study was to evaluate thegrowth and physiological quality of ‘Robusta’ coffee seedlings produced from propagules (stem cuttings) with different cuttingages. The study was conducted in a greenhouse, in the district of Ouro Preto do Oeste, in Rondônia, Brazil (10˚45’43” S and62˚15’10” W). The ages of the cuttings were 30, 60, 90, 120 and 150 days, corresponding to five positions on the secondaryorthotropic stem (sprout), from the apex to the base. Dry matter accumulation, and relative and absolute growth rates wereevaluated for 188 days after cutting, as well as the vegetative characteristics of the seedlings at 125 days after cutting. Itappears that growth can be divided into three phases: 1) Initial: slow growth, lasting approximately 83 days; 2) Intermediate:fast growth, lasting approximately 40 days; and 3) Final: slow growth, starting approximately 125 days after cutting. Withphysiological quality, although all the cuttings showed similar growth curves, those of 60, 90 and 120 days produced, 125 daysafter cutting, the best vegetative performance in the seedlings.